Assessing Pain in Infancy: The Caregiver Context. (2009) - Riddell, R Pillai; Racine, Nicole
Abstract : BACKGROUND: Pain is largely accepted as being influenced by social context. Unlike most other developmental stages throughout the lifespan, infancy is marked by complete dependence on the caregiver. The present paper discusses the primary importance of understanding the caregiver context when assessing infant pain expression. OBJECTIVES: Based on a review of research from both the infant pain and infant mental health fields, three lines of evidence are presented. First, pain assessment is as subjective as the pain experience itself. Second, assessors must be cognizant of the relationship between infant pain expression, and caregiver sensitivity and emotional displays. Finally, larger systemic factors of the infant (such as caregiver relationship styles, caregiver psychological distress or caregiver acculturative stress) directly impact on infant expression. CONCLUSIONS: As a result of infants' inability to give a self-report of their pain experience, caregivers play a crucial role in assessing the pain and taking appropriate action to manage it. Caregiver behaviours and predispositions have been shown to have a significant impact on infant pain reactivity and, accordingly, should not be ignored when assessing the infant in pain.